Lrba participates in the differentiation of IgA+ B lymphocytes through TGFβR signaling - Flores-Hermenegildo, José Mizael; Hernández-Cázares, Felipe de Jesús; Pérez-Pérez, Daniela; Romero-Ramírez, Héctor; Rodríguez-Alba, Juan Carlos; Licona-Limon, Paula; Kilimann, Manfred W.; Santos-Argumedo, Leopoldo; López-Herrera, Gabriela (Frontiers in Immunology, 2024)
Introduction: Lrba is a cytoplasmic protein involved in vesicular trafficking. Lrba-deficient (Lrba-/-) mice exhibit substantially higher levels of IgA in both serum and feces than wild-type (WT) mice. Transforming growth factor β1 (TGFβ1) and its receptors (TGFβR I and II) is essential for differentiating IgA+ B cells. Furthermore, increased IgA production suggests a potential connection between Lrba and the TGFβR signaling pathway in IgA production. However, the specific function of Lrba in B cell biology remains unknown. Aim. Given the increased IgA levels in Lrba-/- mice, the goal in this work was to explore the lymph organs where the switch to IgA occurs, and if TGFβR function is affected. Methods: Non-immunized Lrba-/- mice were compared with Lrba+/+ mice. IgA levels in the serum and feces, as well as during peripheral B cell development, were determined. IgA+ B cells and plasma cells were assessed in the small intestine and secondary lymphoid organs, such as the spleen, mesenteric lymph nodes, and Peyer's patches. The TGFβR signaling pathway was evaluated by determining the expression of TGFβR on B cells. Additionally, SMAD2 phosphorylation was measured under basal conditions and in response to recombinant TGFβ. Finally, confocal microscopy was performed to investigate a possible interaction between Lrba and TGFβR in B cells. Results: Lrba-/- mice exhibited significantly higher levels of circulating IgA, IgA+ B, and plasma cells than in peripheral lymphoid organs those in WT mice. TGFβR expression on the membrane of B cells was similar in both Lrba-/- and Lrba+/+ mice. However, intracellular TGFβR expression was reduced in Lrba-/- mice. SMAD2 phosphorylation showed increased levels under basal conditions; stimulation with recombinant TGFβ elicited a poorer response than in that in Lrba+/+ B cells. Finally, we found that Lrba colocalizes with TGFβR in B cells. Conclusion: Lrba is essential in controlling TGFβR signaling, subsequently regulating SMAD2 phosphorylation on B cells. This mechanism may explain the increased differentiation of IgA+ B cells and production of IgA-producing plasma cells.